Investigation of Chagas disease within the same family: case study - Takamiya, Nayore Tamie [UNESP]; Costa, Erika Alessandra P. N. [UNESP]; Lucheis, Simone B. [UNESP]; Santos, Rodrigo M. [UNESP] (Sociedade Brasileira de Patologia Clínica; Sociedade Brasileira de Patologia; Sociedade Brasileira de Citopatologia, 2020)
Chagas disease (CD) is a neglected endemic disease. Its classic form of transmission occurs through hematophagous triatomine insects. Its classic form of transmission occurs through hematophagous triatomine insects. There are cases of the disease in non-endemic regions that occur through alternative transmissions, as this possibility also exists. The aim of this study was to report a case among members of a same family (born and resident in Taquarituba, São Paulo, Brazil) diagnosed with CD. The family matriarch lived in a mud house in the countryside and reported contact with the triatomine during childhood. Two grown-up children are also seroreactive; both reported not having contact with the insect as children. Medical record analyzes and new laboratory tests were performed. Clinical history and recent tests have confirmed positivity for CD in the matriarch and her grown-up children. Parasitological techniques have shown negative results, evidencing that they are in the chronic form of the disease. Congenital transmission may have occurred between them, as well as the possibility of vector transmission by secondary species cannot be ruled out, since the patients come from a municipality considered endemic for CD in the past.

La enfermedadde Chagas (EC) es una infección endémica que ha sido descuidada. Su forma clásica de transmisión ocurre mediante insectos triatominos hematófagos. Hay casos de la enfermedad en regiones no endémicas que ocurrieron por vías alternativas de transmisión, puesto que también hay esa posibilidad. El objetivo de este estudio fue reportar un caso de miembros de una misma familia diagnosticados con EC. La matriarca de la familia vivía en una casa hecha de barro en la zona ruraly reportó contacto con el triatomino en su infancia. Dos hijosson también sero-reactivos, pero no reportaron contacto con el insecto cuando eran ninos. Se hicieron análisis de historial médico y nuevaspruebas de laboratorio. El histórico clínico y laspruebas recientes confirmaran la positividad para EC, tanto en la madre como en los hijos. Las técnicasparasitológicas demostraron resultados negativos, comprobando la forma crónica de la enfermedad. Transmisión congénitapuede haber ocurrido entre ellos, así como no se puede descartar la posibilidad de ocurrencia de transmisión vectorial por especies secundarias, ya que los pacientes proceden de un municipio que fue considerado endémico para EC en el pasado.
Keywords: congenital Chagas disease; Trypanosoma cruzi; mechanism of transmission; diagnostic methods